Peculiarity of Diabetes in Presentation Characteristics and Outcomes in Patients With Acute Myocardial Infarction Undergoing Primary Percutaneous Coronary Intervention in Tertiary Care Cardiac Centre - Ullah, Ihsan; Wadood, Atta Ul; Ullah, Shafi; Zeb, Shah; Rahman, Sajjad Ur; Aitzaz, Muhammad; Khan, Sana Ullah; Zeb, Hasan; Yar, Sultan Hikmat; Raza, Ali (Biological and Clinical Sciences Research Journal, 2025)
Diabetes mellitus (DM) is a major risk factor for cardiovascular diseases. Atypical and late presentations in people with diabetes pose a danger of delayed diagnosis, treatment, interventions, and, as a result, worse outcomes. In patients with AMI undergoing Primary PCI(PPCI), people with diabetes are prone to high thrombus burden and procedural complications. A registry revealed to have a high thrombus burden, high mortality, and delays in interventions. Studies have shown that patients with type 2 diabetes mellitus (T2DM) combined with AMI are in a high-risk group for no-reflow Phenomena because these patients usually have complex coronary artery diseases. Objective: This study aims to systematically assess the presentation characteristics and outcomes of diabetic patients who presented with AMI Undergoing Primary PCI. Method: A retrospective cohort study was conducted on 422 patients admitted with AMI who underwent PPCI. Patients’ data were taken from electronic health records (HMIS)-demographics, presentation, and PPCI data. The Primary outcomes evaluated were in-hospital mortality and PPCI-related complications. Results: Out of 422 patients, 33.6% were diabetic and 66.3% were non-diabetic. Diabetic patients had a higher mean age, longer symptoms to hospital visit duration (9.11 hours vs 8.84 hours), more multivessel disease (28% vs 16.7%), and a higher heavy thrombus burden. Despite presenting later, door-to-balloon times were similar. People with diabetes had lower TIMI-III flow rates (23.4% vs 30.36% in nondiabetics), lower complete revascularization rates, and higher MACE incidence. Conclusion: Diabetic patients with AMI show distinct clinical characteristics and significantly worse outcomes compared to nondiabetics, highlighting the need for heightened clinical suspicion, rapid diagnostics, aggressive early management, and future interventions to improve timely access to care and optimize long-term management for this high-risk population.